PENDEKATAN KONSELING RASIONAL EMOTIF DALAM MENGEMBANGKAN BODY POSITIVITY PADA REMAJA DENGAN GANGGUAN CITRA TUBUH: STUDI KASUS PADA SISWA DI SMAN 23 MAKASSAR - Akhsanun Nisa; Abdul Saman; Fitriana; Maslina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the presence of adolescents who experience body image disorders, such as dissatisfaction with physical appearance, shame, low selfesteem, and avoidance behavior in social situations. This study aims to describe the forms and characteristics of body image disorders, understand students' interpretations of the concept of body positivity, and analyze the role of the Rational Emotive Behavior Therapy (REBT) approach in developing body positivity in adolescents. The research used a qualitative approach with a case study type. The research subjects consisted of two students of SMAN 23 Makassar, namely AM and NWY. Data were collected through in-depth interviews, observation, documentation, and literature studies, then analyzed through data reduction, data presentation, and drawing conclusions. The results showed that the two subjects had irrational beliefs about their bodies that gave rise to negative emotions and avoidance behavior. After participating in REBT counseling through the techniques of disputing irrational beliefs, self-reflection, and homework assignments, the subjects showed cognitive, emotional, and behavioral changes. They were better able to accept their body condition, reduce social comparison, and increase self-confidence. Thus, the Rational Emotive Counseling approach is effective in developing body positivity in adolescents with body image disturbances.